Consultation of government officials and community leaders on the Climate Action Initiative in Sri Lanka - Alahacoon, Niranga; Amarnath, Giriraj; Amarasinghe, Upali A. (International Water Management Institute, 2025)
As climate impacts intensify, Sri Lanka confronts increasing flood and drought risks that threaten agricultural livelihoods and food security. Under the CGIAR Climate Action Program, the International Water Management Institute (IWMI) held a two-day field consultation in Anuradhapura to align community perspectives and government priorities for a Climate Action Science Program. The consultation sought to identify priority intervention sites, suitable climate-resilient practices, irrigation schemes for water-use assessments, and farmers’ readiness to adopt new approaches. Day One brought together local government officers, farmer leaders, and progressive producers to discuss operational challenges. The government officials introduced major challenges, such as poor canal maintenance, fragmented and uneven plots, limited access to quality seeds, and reluctance to diversify beyond paddy. Farmer leaders highlighted successful examples of high-value and climate-smart cultivation that could be scaled. Field visits illustrated site-specific practices such as rainfed high value cropping and controlled chili production. Day Two convened senior officials, including the District Secretary and the Governor, enabling strategic dialogue to mainstream findings into provincial planning. The meetings produced clear action points: stakeholder awareness meetings, a provincial launch of the Climate Science Program, formation of a consultative group, and selection of additional tank systems for pilot interventions.